Influence of the lack of a standard definition of “family business” on research into their international strategies73 - Myriam Cano-Rubio; Guadalupe Fuentes-Lombardo; Manuel Carlos Vallejo-Martos (European Research on Management and Business Economics (ERMBE), 2017)
Research into the internationalisation strategies of family businesses is plagued by the excessive use of many and varied concepts to define these companies, and often leads to diverse and disparate results. The conceptual spectrum used by researchers is very broad, ranging from the simplest definition, in which a company is classified as a family business on the basis of the perception of its owners and/or managers, to others which consider variables such as ownership, management, involvement of the family in the business, continuity and combinations thereof. The results obtained highlight the need for those researching family business internationalisation strategies to use a standard definition of family business, so enabling us to continue advancing in our knowledge of this topic and avoid coming to different conclusions merely as a result of having based our research on different definitions.
Keywords: M16; 650; Family business; Definition; International strategy; Wine sector; Olive-oil sector